Associative properties of poly(ethylene glycol)–poly(vinyl acetate) comb-like graft copolymers in water. Issue 14 (21st March 2019) - Mamusa, Marianna; Tempesti, Paolo; Bartolini, Arianna; Carretti, Emiliano; Ghobadi, Ahmad F.; Smets, Johan; Aouad, Yousef G.; Baglioni, Piero
Abstract : A PEG- graft -PVAc comb-like copolymer in water forms spherical single-chain nanoparticles that transition towards hierarchically complex structures with increasing polymer concentration. Abstract : The self-assembly of amphiphilic graft copolymers is generally reported for polymer melts or polymers deposited onto surfaces, while a small number of cases deal with binary mixtures with water. We report on the associative properties of poly(ethylene glycol)- graft -poly(vinyl acetate) (PEG- g -PVAc) comb-like copolymers in water, demonstrating the existence of a percolative behaviour when increasing the PEG- g -PVAc content. Rheology, light- and small-angle X-ray scattering experiments, together with dissipative particle dynamics simulations, reveal a progressive transition from spherical polymer single-chain nanoparticles (SCNPs) towards hierarchically complex structures as the weight fraction of the polymer in water increases. The ability of PEG- g -PVAc to attain different nano- and microstructures is of great importance in numerous applications such as in the fields of cosmetics, detergency and drug delivery.